China Scholarship 2021 Online Mandarin programme of Hebei University - Mritha, Ramalingam (Faculty of Computing, 2021)
PEKAN, 22 August 2021 - Congratulations to undergraduate students of FK UMP who have participated in Online Mandarin Programme of Hebei University under China Scholarship for 2021.